2018
DOI: 10.3390/tropicalmed3040111
|View full text |Cite
|
Sign up to set email alerts
|

Low Praziquantel Treatment Coverage for Schistosoma mansoni in Mayuge District, Uganda, Due to the Absence of Treatment Opportunities, Rather Than Systematic Non-Compliance

Abstract: The World Health Organization (WHO) recommends praziquantel mass drug administration (MDA) to control schistosomiasis in endemic regions. We aimed to quantify recent and lifetime praziquantel coverage, and reasons for non-treatment, at an individual level to guide policy recommendations to help Uganda reach WHO goals. Cross-sectional household surveys (n = 681) encompassing 3208 individuals (adults and children) were conducted in 2017 in Bugoto A and B, Mayuge District, Uganda. Participants were asked if they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 44 publications
5
78
3
Order By: Relevance
“…Reasons for this are unclear, but could be due to concerns about taking during pregnancy or a belief that they are less likely to have schistosomiasis due to less frequent or obvious lake contact [ 26 ]. Our results contrast with studies from other settings that have found little difference in treatment receipt by age and, or gender [ 16 , 17 ], instead finding that factors such as socio-economic status and sanitation had greater predictive utility; unfortunately we did not collect information on these variables on the treatment registers in our study so could not investigate them further. Further qualitative work is needed to provide insight and understanding of these patterns.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Reasons for this are unclear, but could be due to concerns about taking during pregnancy or a belief that they are less likely to have schistosomiasis due to less frequent or obvious lake contact [ 26 ]. Our results contrast with studies from other settings that have found little difference in treatment receipt by age and, or gender [ 16 , 17 ], instead finding that factors such as socio-economic status and sanitation had greater predictive utility; unfortunately we did not collect information on these variables on the treatment registers in our study so could not investigate them further. Further qualitative work is needed to provide insight and understanding of these patterns.…”
Section: Discussioncontrasting
confidence: 99%
“…Absence during treatment rounds was by far the most common reason for not receiving MDA. This is consistent with findings from Mayuge District in Uganda [ 16 ], where non-receipt of treatment was more likely to be due to not being offered treatment rather than systematic non-compliance. In our trial, every effort was made to advertise the forthcoming treatment and offer multiple opportunities of receiving it, but despite this, coverage remained sub-optimal.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…4 Problems with both measuring MDA coverage and achieving targets have been reported previously. [5][6][7] The Schistosomiasis Consortium for Operational Research and Evaluation (SCORE) was launched in 2008 with funding from the Bill & Melinda Gates Foundation to contribute to the evidence base for programmatic decision-making related to schistosomiasis control and elimination. The SCORE research portfolio includes studies related to topics such as control and elimination of schistosomiasis, diagnostic test development and validation in real-world settings, and changes in schistosome population genetics in response to drug pressure.…”
Section: Introductionmentioning
confidence: 99%